2021
DOI: 10.1021/jacs.1c08976
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic C-Terminal Protein Engineering with Amines

Abstract: Chemoenzymatic protein and peptide modification is a powerful means of generating defined, homogeneous conjugates for a range of applications. However, the use of transpeptidases is limited by the need to prepare synthetic peptide conjugates to be ligated, bulky recognition tags remaining in the product, and inefficient substrate turnover. Here, we report a peptide/protein labeling strategy that utilizes a promiscuous, engineered transpeptidase to irreversibly incorporate diverse, commercially available amines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…A recent protein labeling work showed that OaAEP1(C247A) could directly catalyze the attachment of a small molecule with a primary amine to a protein via its C-terminal NGL sequence. 21 Thus, we hypothesize that a surface covered with primary amino may also be reacted with properly designed target protein directly catalyzed by AEP, and a much more convenient one-step of protein immobilization may be achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent protein labeling work showed that OaAEP1(C247A) could directly catalyze the attachment of a small molecule with a primary amine to a protein via its C-terminal NGL sequence. 21 Thus, we hypothesize that a surface covered with primary amino may also be reacted with properly designed target protein directly catalyzed by AEP, and a much more convenient one-step of protein immobilization may be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the target protein can be immobilized on an amino-functionalized surface in one step. 21 We tested and applied these methods to atomic force microscopy-based single-molecule force spectroscopy. Force spectroscopy is a powerful tool that can mechanically manipulate a single molecule and study its corresponding conformational changes or interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide ligases have been widely used in protein labelling and cyclic peptide synthesis in recent years [6,[19][20][21][22][23][24][25][26]. To characterize various known peptide ligases or identify new ones, in the present study we developed a general bioluminescent activity assay based on an inactive large NanoLuc fragment (LgBiT) and a low-affinity SmBiT complementation tag.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Asparaginyl ligases are remarkably versatile enzymes-they have been employed for peptide and protein head-to-tail cyclization, [6] N-or Cterminal protein labeling with small synthetic peptides, [7] the generation of N-to-C protein-protein fusions, including polyproteins, [8] the promiscuous modification of protein Ntermini on red blood cell and extracellular vesicle surfaces, [9] and for C-terminal protein labeling with structurally diverse, non-peptidyl amines. [20] However, like all known transpeptidases, asparaginyl ligases have, until now, been thought to be constrained to operating on α-amino acid substrates and in the N-to-C orientation. Here we expand the synthetic scope of asparaginyl ligase-catalyzed reactions via substrate mimetics, enabling intermolecular ligation at L-/D-and α-/βamino acid ligation junctions and C-to-C protein fusions.…”
Section: Introductionmentioning
confidence: 99%